1999
DOI: 10.1089/gte.1999.3.223
|View full text |Cite
|
Sign up to set email alerts
|

BRCAl Screening in Patients with a Family History of Breast or Ovarian Cancer

Abstract: Several studies have shown that the frequency of BRCA1 mutations in high-risk families differs widely between populations. In a recently published study from the Stockholm region, we found BRCA1 mutations in about 35% of the breast/ovarian families, but only in 1% of the families with site-specific breast cancer. To determine the frequency of BRCA1 mutations in families with a less increased risk for breast or ovarian cancer, a second study was performed. A total of 94 families with two and six families with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
0
11
1
Order By: Relevance
“…The prevalence found in our study is the lowest of all studies on unselected breast cancer patients, probably reflecting the comparatively low rates detected also in high-risk breast cancer families from the region (Zelada- Hedman et al, 1997;Arver et al, 1999Arver et al, , 2001. Both mutations were found in patients with a family history of both breast and ovarian cancer, rendering them the most likely to segregate BRCA1 mutations, and these patients should have been offered genetic counseling.…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations
“…The prevalence found in our study is the lowest of all studies on unselected breast cancer patients, probably reflecting the comparatively low rates detected also in high-risk breast cancer families from the region (Zelada- Hedman et al, 1997;Arver et al, 1999Arver et al, , 2001. Both mutations were found in patients with a family history of both breast and ovarian cancer, rendering them the most likely to segregate BRCA1 mutations, and these patients should have been offered genetic counseling.…”
Section: Resultscontrasting
confidence: 53%
“…In breast-ovarian families in this region, two studies have reported a mutation frequency of 34% (Zelada-Hedman et al, 1997;and Arver et al, 2001). In Stockholm breast cancer families in which age was not used for selection, only a 1% frequency of mutations was found (Zelada-Hedman et al, 1997;Arver et al, 1999). In a recent study, when age criteria were added, 7% frequency of mutations was detected in breast cancer-only families, whereas a 34% frequency of mutations was found in breastovarian cancer families (Arver et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No case of exon 13 duplication was found [16]. In the Stockholm region, germline mutations in BRCA1 and 2 are found only in a third of all familial breast-ovarian and in 10% of familial breast cancer cases, leaving a major proportion of all hereditary cases unexplained [18,19]. To check if BRCA1 ins6kbEx13 could explain a proportion of these cases and to further estimate the prevalence of this duplication in Swedish breast/breastovarian cancer families, we screened patients from a set of 142 breast cancer and 52 breast-ovarian cancer families for BRCA1 ins6kbEx13.…”
mentioning
confidence: 99%
“…First, previous publications on the genetic background of breast cancer indicate heterogeneity in different populations (the prevalence of BRCA1 and 2 mutations varies for example considerably) [37]. There are several studies on the BRCA1 and 2 mutation prevalence in high-risk breast cancer families from Stockholm, based on selected families from the Clinic of Genetics, but less is known about the frequency of family history in unselected breast cancer patients, and how, if at all, it influences other parameters related to their breast cancer [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%